2007
DOI: 10.1007/bf03216859
|View full text |Cite
|
Sign up to set email alerts
|

A framework for research into Australian middle school practice

Abstract: As a new reform in Australian education, middle schooling has been gaining momentum. The rationale behind middle schooling is to bridge the traditional primaryhigh school gap and provide a more developmentally appropriate educational experience for young adolescents. Middle schooling in the USA has gone through a "boom-to-bust" cycle and is currently undergoing a "reinvention" as research on practice and reporting of research on practice has, in the most part, been ad hoc and piecemeal. If Australian middle sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 6 publications
0
11
0
Order By: Relevance
“…The National Middle Schooling Project found that a significant number of middle school students are not deriving benefits from schooling (Barratt, 1998). Main and Bryer, (2007) contend that in "Australian schools, middle schooling has become a popular educational reform that aims to meet the academic and socio-emotional developmental needs of young adolescents" (p. 91).…”
Section: Research Questionmentioning
confidence: 99%
“…The National Middle Schooling Project found that a significant number of middle school students are not deriving benefits from schooling (Barratt, 1998). Main and Bryer, (2007) contend that in "Australian schools, middle schooling has become a popular educational reform that aims to meet the academic and socio-emotional developmental needs of young adolescents" (p. 91).…”
Section: Research Questionmentioning
confidence: 99%
“…Subsequently, proponents of such a philosophy linked it with efforts for socially just educational reform (Barratt, 1998;Brennan & Sachs, 1998;Cormack et al, 1998) through emphasising the importance of student engagement in order to avoid alienation, and arguing for greater pastoral care, student consultation and genuine decision-making opportunities (Cormack, 1996(Cormack, , 1998. Since that time, advocacy for a Middle Schooling philosophy of social equity, meeting student needs, supporting identity development, improving transition and boosting retention through the provision of quality teaching and learning for all, has y continued to grow in Australia (Carrington, 2006;Groundwater-Smith, Mitchell, & Mockler, 2007;Lingard, 2007;Main & Bryer, 2007;Smyth & McInerney, 2007).…”
Section: Middle Years Education In Australiamentioning
confidence: 99%
“…Australian critiques of the Middle Schooling movement have observed that it has been largely rhetorical (lisahunter, 2007) and relied more on advocacy than thorough research (Earl, 1999;Hill & Russell, 1999), with more teacher research needed in particular (Cumming, 1996;Main & Bryer, 2007). Meanwhile, it has been noted that there has been a lack of attention to student views in the development of a Middle Schooling philosophy that is supposedly student-centred (Main & Bryer, 2007;Powell, 2001), as well as relatively few opportunities for students to influence the direction of activities in classrooms (Lingard, 2007).…”
Section: Middle Years Education In Australiamentioning
confidence: 99%
See 1 more Smart Citation
“…Several of these factors have also been considered influential: (1) leadership in the local administration (Datnow 2005;Gersten et al 2000;Harmon et al 2007;Main and Bryer 2007;Sindelar et al 2006;Stevens 2004), (2) provision of adequate resources (Datnow 2005;Hargreaves and Fink 2003;Harmon et al 2007;Main and Bryer 2007;McIntyre and Kyle 2006;Taylor 2006), (3) standardization of reform (Giles and Hargreaves 2006;Goodson et al 2006;Grimes et al 2006;Guhn 2009;Hargreaves and Goodson 2006;Stringfield et al 2008), and (4) high stakes tests and the resultant pressure (Datnow 2005;Gersten et al 2000).…”
Section: Introductionmentioning
confidence: 98%